Indoor Environmental Quality (IEQ) and occupant's perception in Malaysian green office buildings / Sati Sekar Kinanthi, Zulkiflee Abdul Samad, Faizul A. Rahim - Kinanthi, Sati Sekar; Abdul Samad, Zulkiflee; A. Rahim, Faizul (Faculty of Architecture, Planning & Surveying and UiTM Press, 2013)
Natural elements used as a part of sustainable building design have been known to improve the Indoor Environment Quality (IEQ) of a space, and enhance occupants' physical and psychological well-being. This study addresses the impact of green office buildings on occupants' perception of their working area, productivity, mood, sense of well-being, and work motivation, with the aim of understanding the workability of sustainable design employed in Malaysia. An embedded multiple-case case study was conducted. Pictures and data of the green building design were collected, and cross-case analysis was conducted to compare the design elements among the three buildings. A total of 210 subjects in the 3 buildings completed a questionnaire about their perception of the IEQ of their working space, and the perceived psychological impact. Finally, interviews were conducted on 5 subjects per building to further understand their perception of the buildings and how they feel like they are affected by it. The result showed that overall, the subjects perceive sustainable office buildings as optimal to their comfort level, and that the buildings affect their physical and mental well-being positively.